1986
DOI: 10.1177/0261927x8600500402
|View full text |Cite
|
Sign up to set email alerts
|

Goal Types, Compliance-Gaining and Locus of Control

Abstract: This study argues that situations can be conceptualised according to actors' prototypes (Cantor & Mischel, 1979a, b) for obtaining goals. In addition, these goals are constructed from salient dimensions of perceptions found in previous literature on compliance-gaining. Fourteen goal types were selected and used in a study concerning perceptions of influence situations and expected use of influence approaches. Perceptions and influence strategies varied from one goal to another, and Locus of Control constructs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 40 publications
0
29
0
Order By: Relevance
“…Ralston (1985) proposed that since internals believe they can control their environment, they should be more likely to use ingratiatory tactics than would externals. However, Canary, Cody and Marston (1986) concluded that powerless actors tend to prefer compliance-gaining situations in which they are dependent on the target and can exploit that dependence by manipulating the target's emotions (positively or negatively), or by manipulating relational or exchange obligations (i.e. invoking norms of reciprocity and feelings of obligation; Pfeer, 1992).…”
Section: Conditions Associated With Use Of a Soft Strategymentioning
confidence: 99%
“…Ralston (1985) proposed that since internals believe they can control their environment, they should be more likely to use ingratiatory tactics than would externals. However, Canary, Cody and Marston (1986) concluded that powerless actors tend to prefer compliance-gaining situations in which they are dependent on the target and can exploit that dependence by manipulating the target's emotions (positively or negatively), or by manipulating relational or exchange obligations (i.e. invoking norms of reciprocity and feelings of obligation; Pfeer, 1992).…”
Section: Conditions Associated With Use Of a Soft Strategymentioning
confidence: 99%
“…Goal type=situation Fourteen common situations, each with a desired goal and complemented by an example, served as the goal type instrument (Canary, Cody, & Marston, 1986). For example, in the situation entitled ''Routine Activities-Friends,'' the general goal listed was to have a routine night out with friends.…”
Section: Goal Types and Strategy Selectionmentioning
confidence: 99%
“…completed numerous investigations aimed at categorizing common goal types (Canary, Cody, & Marston, 1986;Cody & McLaughlin, 1980;Cody, Woelfel, & Jordan, 1983). Canary, Cody, and Marston (1986) identified fourteen different types of goals a person might have in a social interaction, such as initiating a relationship or gaining assistance from a professor.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Locus of control specific to particular interpersonal goals has long been advocated as a superior assessment of control expectancies (Canary, Cody, & Marston, 1986;Canary et al, 1988;Dudley, 1977;Hamilton 1991;Lefcourt, 1981Lefcourt, ,1982Lefcourt, von Bayer, Ware, & Cox, 1979;Paulhus, 1983;Paulhus & Christie, 1981). The study of locus of control with regard to conflict-specific goals was forwarded by Canary et al (1988).…”
Section: Conflict Control Expectanciesmentioning
confidence: 99%